STUDENTS’ DIFFICULTIES IN SOLVING HIGHER-ORDER THINKING SKILLS (HOTS) READING COMPREHENSION SECTION AT SMA 1 TAKENGON - Yunie Amalia Rakhmyta; Alif Maulidiyah (Jurnal As-Salam, 2021)
This study aims to determine students’ difficulties in solving Higher-Order Thinking Skills (HOTS) questions and their dominance due to the reading comprehension section at SMAN 1 Takengon. This study was delivered through a qualitative descriptive research design. Twenty-two students were elected to be research subjects based on purposive sampling. The instruments were documentation and interview. Data analyzed by adopting Miles and Huberman’s theory stepped into three-phase; data reduction, data display, and conclusion.  As a result, the percentages showed several students’ difficulties; first in making inferences about 48%, second, determining the main idea about 26%, third, in detailed information about 18%, last, in understanding vocabulary about 8%. In conclusion, the dominant difficulty is making an inference.